DETERMINAN INFLASI REGIONAL KOTA-KOTA DI PROVINSI JAWA BARAT TAHUN 2000 - 2009 - Falianty, Telisa Aulia; Hanifah, Luthfi (Badan kebijakan Fiskal, 2012)
This research is intended to analyze determining variables of regional inflation at cities of West Java Province during 2000 - 2009. This study is motivated by the facts that inflation is known as an important indicator for economic development planning. Therefore, managing inflation rate become important for government to arrange their national development planning. Managing national inflation should follow whit managing regional inflation. Thus, identijying regional inflation determining variables become important process for managing phase of regional inflation. Approximation for regional inflation determining variable are monetary variables and non monetary variables. Monetary variables consist of real interest rate, while non monetary variables consist of regional indigenous income (PAD), regional expenditure, infrastructure condition, minimum wages rate, and inflation rate of DKl Jakarta. Method research for analysis is utilizes data panel regression Of G2SLS (Generalized two stage least square) with fixed effect method. The findings of this study point out that regional inflation at cities of West Java Province significantly affected by real interest rate, minimum wages rate, infrastructure condition, inflation rate of DKl Jakarta, regional indigenous income (PAD), and regional expenditure. Thus, shown that cost push effect system and demand pull effect system is work on to determine regional inflation at cities of West Java Province. This research also finding that regional that regional interaction is influencing regional inflation rate as shown on interaction between DKl Jakarta Province and cities in West Java Province which presumtive cause by distribution system of goods, commodity, and services from production area to consumption area.